EFEKTIVITAS KINERJA PENGHUBUNG KOMISI YUDISIAL DALAM PENGAWASAN PERILAKU HAKIM DI SUMATERA SELATAN - subrata, subrata subrata (Faculty of Law, University of Palembang, 2024)
This study examines the effectiveness of the Judicial Commission Liaisons' performance in assisting the implementation of the Judicial Commission's duties in monitoring and supervising judges' behavior in South Sumatera. Considering the vast area and limited human resources, this study evaluates the extent to which these factors influence the effectiveness of the liaisons' performance in fulfilling their functions. Using a descriptive qualitative method, data were obtained through in-depth interviews, observations, and documentation studies. The results show that human resource limitations and the extensive work area are the main obstacles to effective supervision. However, optimizing resources and improving work procedures can enhance the effectiveness of the liaisons' performance. This study provides recommendations to improve supervision strategies and enhance the capacity of the liaisons through training and the development of more efficient work procedures. Keywords: Judicial Commission Liaisons; Performance Effectiveness; Judge Supervision; Monitoring; Judge Behavior.